Suggested reading list. Novels, plays, biographies, poetry dealing with social and economic problems. Prepared by the Continuation Committee on the pooling of material for workers' classes, elected by the eighth annual Conference of Teachers in Workers' Education held at Brookwood Labor College under the auspices of the Brookwood Local American Federation of Teachers (Affiliated Schools for Workers, 1933)
Stencil.